Penegakan Hukum terhadap Pelaku Tindak Pidana Incest dengan Korban Anak : Studi Kasus Putusan Nomor 139/Pid.B/2016/PN LBO - Aristia Gani; Moonti, Roy Marthen (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
This study aims to analyze law enforcement against perpetrators of incest crimes involving child victims and the considerations of the Panel of Judges in Decision Number 139/Pid.B/2016/PN Lbo. The research employs an empirical legal method with an empirical juridical approach. Data were collected through library research and field research at the Gorontalo Regional Police, Gorontalo High Prosecutor's Office, and Limboto District Court. Primary data were obtained through interviews with law enforcement officers, while secondary data were sourced from legal regulations, case documents, and relevant literature. Data were analyzed qualitatively. The results show that the handling of incest crimes is conducted through investigation, prosecution, and trial stages based on criminal procedure law and child protection regulations. The process involves coordination among investigators, prosecutors, and child protection institutions. However, several obstacles remain, including the victim’s psychological condition, family relationships with the perpetrator, changes in statements during examination, and difficulties in evidence collection due to repeated acts committed in private spaces. The judge’s sentencing considerations were considered insufficient in reflecting justice because the punishment was lighter than the prosecutor’s demand. The study concludes that law enforcement follows applicable mechanisms, but its effectiveness remains influenced by challenges in evidence and victim protection.